On the Kauffman-Harary conjecture for Alexander quandle colorings - Asami, Soichiro (Revista Matemática Complutense, 2006)
The Kauffman-Harary conjecture is a conjecture for Fox’s colorings of alternating knots with prime determinants. We consider a conjecture for Alexander quandle colorings by referring to the Kauffman-Harary conjecture. We prove that this new conjecture is true for twist knots.